Testing for pre- and post-copulatory inbreeding avoidance in the flour beetle Tribolium castaneum - Fathi Ali Attia; Tom Tregenza; Ramakrishnan Vasudeva (PLoS ONE, 2026)
Inbreeding depression poses a significant threat to fitness in many taxonomic groups. Studies have suggested that females may mate with multiple males to reduce inbreeding through post-copulatory discrimination against closely related males. Stored product pests are a group where inbreeding risk may arise frequently as small numbers colonies patchily distributed resources. We examined potential pre- and post-copulatory inbreeding avoidance in the red flour beetle Tribolium castaneous using direct observation of breeding behaviour and subsequent scoring of offspring parentage using phenotypical markers . Contrary to expectations, males courted and mated with related females slightly more frequently than with unrelated females. Offspring of unrelated parents were more likely to survive to adulthood, meaning that males unrelated to their mate had a higher number of adult offspring when competing for fertilisations with a male who was a full sibling to the female. When the lower survival of inbred offspring was accounted for, there was no difference in the estimated fertilisation success of males in relation to whether or not they were related to their mate. The second male to mate initially gained the majority of fertilisations, but this declined so that by week five, first and second males had similar fertilisation success. This suggests that sperm precedence in this species includes some effects of both sperm displacement and stratification of sperm within the spermatheca. We discuss our observation of a preference for mating with siblings combined with evidence for inbreeding depression in the context of potential inclusive fitness benefits of kin mating.